Intelligent computer mathematics : 11th International conference, AISC 2012, 19th symposium, calculemus 2012, 5th International Workshop, DML 2012, 11th International Conference, MKM 2012, Systems and Projects, Held as Part of CICM 2012, Bremen, Germany, July 8-13, 2012. Proceedings - Jeuring, Johan (Lecture Notes in Computer Science, 2012)
This book constitutes the joint refereed proceedings of the 11th International Conference on Artificial Intelligence and Symbolic Computation, AISC 2012, 19th Symposium on the Integration of Symbolic Computation and Mechanized Reasoning, Calculemus 2012, 5th International Workshop on Digital Mathematics Libraries, DML 2012, 11th International Conference on Mathematical Knowledge Management, MKM 2012, Systems and Projects, held in Bremen, Germany as CICM 2012, the Conferences on Intelligent Computer Mathematics. The 13 revised full papers out of 19 submissions for MKM 2012, 6 revised full papers out of 9 submissions for Calculemus 2012, 6 revised full papers out of 8 submissions for AISC 2012, 2 revised full papers out of 3 submissions for DML 2012, and 11 revised full papers out of 12 submissions for Systems and Project track presented were carefully reviewed and selected, resulting in 38 papers from a total of 52 submissions.